Long-term pituitary function following transsphenoidal surgery for non-functional pituitary neuroendocrine tumor with apoplexy: a single-center retrospective analysis - Dongbo Zou; Yongxiang Yang; Ruiting Gao; Yangqing Ou; Jianing Luo; Zhi Zhang; Tao Yang; Jingmin Cheng (Scientific Reports)
Abstract This retrospective study aims to investigate pituitary function 3 years after transsphenoidal surgery in patients with non-functional pituitary neuroendocrine tumor(NF-PitNET) complicated by apoplexy. A retrospective analysis was performed on patients with NF-PitNET who underwent transsphenoidal surgery from January 2016 to September 2020. The patients were divided into apoplexy group and non-apoplexy group based on magnetic resonance imaging(MRI), surgical, and pathological findings. A comparative analysis of pituitary endocrine function was conducted between the two groups at three years postoperatively. A total of 563 patients were initially screened, and 50 matched pairs were included in the study following propensity score matching.Preoperatively, 35 patients in the apoplexy group exhibited pituitary hormone deficiencies, including 2 cases of panhypopituitarism and 14 cases with deficiencies in two or more hormones.In contrast, the non-apoplexy group had 30 patients with pituitary hormone deficiencies, of which 8 had deficiencies in two or more hormones, with no cases of panhypopituitarism.A significant difference was observed in the incidence of ACTH axis deficiency between the two groups (36% vs. 14%, p = 0.011). This trend persisted at the 3-year follow-up, where the apoplexy group continued to show a significantly higher prevalence of ACTH deficiency (34% vs. 16%, p = 0.038).No significant difference was found in the incidence of preoperative LH/FSH axis insufficiency between the groups (38% vs. 40%, p = 0.838).However, at the 3-year follow-up, the apoplexy group exhibited a significantly higher incidence of LH/FSH axis insufficiency compared to the non-apoplexy group (30% vs. 12%, p = 0.027). Additionally, there was no significant difference in the incidence of deficiencies in two or more hormones between the two groups after 3 years of follow-up (39.1% vs. 27.3%, p = 0.705). Pituitary apoplexy is commonly associated with pituitary insufficiency. Patients with preoperative apoplexy are more susceptible to ACTH axis dysfunction compared to those without apoplexy, and they demonstrate significantly poorer recovery of ACTH axis function following transsphenoidal surgery. Additionally, among patients with apoplexy, the postoperative recovery of LH/FSH axis function is also notably inferior to that observed in non-apoplexy patients.